Problems of Investigators in the Legal Process Against Children as Perpetrators of Abuse - Putri Mulya Pulukadang (Estudiante Law Journal, 2023)
This study aims to determine investigators’ problems in the legal process against children as perpetrators of abuse. The research method used is empirical research descriptive qualitative research approach and using descriptive data analysis techniques. The results of this study indicate that there are two problems faced by investigators in the legal process against children as perpetrators of abuse, namely internal problems,s and external problems. Internal problems of course consist of several things, including investigator resources, the lack of an investigative budget, and the lengthy stages of the legal process. While the external problems faced are the lack of community support, the legal awareness of the community is still minimal, and the problem of evidence and technological developments is increasingly sophisticated.